49.2k views
2 votes
What’s the answer to Y=-2(x-3)^2+1

User Wuwucat
by
5.8k points

1 Answer

7 votes

Answer:

Explanation:

Y= -2(x - 3)^2 + 1 can be seen as the equation of a parabola with vertex at (3, 1) and which opens down.

Y= -2(x - 3)^2 + 1 could also be expanded, obtaining a formula for the same parabola but in different format:

y = -2(x^2 - 6x + 9) + 1, or

y = -2x^2 + 12x -18 + 1, or y = -2x^2 + 12x - 17

User Chockenberry
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.